CIRI GETARAN MEKANIK DAN ARUS CATU PADA MOTOR LISTRIK INDUKSI 3-FASA AKIBAT EKSENTRISITAS CELAH UDARA - Indra Nurhadi; Andi Isra Mahyuddin; M Ahmarudin (Mesin, 2001)
This paper discusses theoretical and experimental study to determine the signature of stator supply current and stator vibration of 3-phase induction motor resulting from airgap eccentricity. Based on the theoretical study it can be formulated that the signature due to eccentricity is affected by number of slots on the rotor and the stator as well as slip, defined as